The speed and acceleration of the ball carrier and tackler into contact during front-on tackles in rugby league - Parmley, J.; Jones, B.; Whitehead, S.; Rennie, G.; Hendricks, S.; Johnston, R.; Collins, N.; Bennett, T.; Weaving, D. (Journal of Sports Sciences, 2023)
The aim was to use a combination of video analysis and microtechnology (10 Hz global positioning system [GPS]) to quantify and compare the speed and acceleration of ball-carriers and tacklers during the pre-contact phase (contact - 0.5s) of the tackle event during rugby league match-play. Data were collected from 44 professional male rugby league players from two Super League clubs across two competitive matches. Tackle events were coded and subject to three stages of inclusion criteria to identify front-on tackles. 10 Hz GPS data was synchronised with video to extract the speed and acceleration of the ball-carrier and tackler into each front-on tackle (n = 214). Linear mixed effects models (effect size [ES], confidence intervals, p-values) compared differences. Overall, ball-carriers (4.73 ± 1.12 m·s-1) had greater speed into front-on tackles than tacklers (2.82 ± 1.07 m·s-1; ES = 1.69). Ball-carriers accelerated (0.67 ± 1.01 m·s-2) into contact whilst tacklers decelerated (-1.26 ± 1.36 m·s-2; ES = 1.74). Positional comparisons showed speed was greater during back vs. back (ES = 0.66) and back vs. forward (ES = 0.40) than forward vs. forward tackle events. Findings can be used to inform strategies to improve performance and player welfare.